Sofosbuvir and ledipasvir improve patient‐reported outcomes in patients co‐infected with hepatitis C and human immunodeficiency virus. Issue 11 (13th June 2016) - Younossi, Z. M.; Stepanova, M.; Sulkowski, M.; Naggie, S.; Henry, L.; Hunt, S.
Summary: A fixed‐dose combination of ledipasvir and sofosbuvir (LDV/SOF) has been approved for treatment of HCV patients. We assessed the effect of LDV/SOF on patient‐reported outcomes (PROs) in HIV–HCV‐co‐infected patients. Patient‐reported outcomes data from HIV–HCV‐co‐infected patients who were treated with LDV/SOF for 12 weeks were collected as a part of a clinical trial (ION‐4). Historical controls were HIV–HCV‐co‐infected patients treated with SOF and ribavirin (RBV) in PHOTON‐1. We included 335 HIV–HCV‐co‐infected patients (SVR‐12 in HCV genotype 1 was 96%) who received LDV/SOF, while 223 patients (SVR‐12 in HCV genotype 1 was 76.3%) received SOF/RBV. During treatment, patients receiving LDV/SOF showed improvement in all of their PRO scores (+6.0% in activity/energy of CLDQ‐HCV, +5.0% in fatigue score of FACIT‐F, +6.8% in physical component of SF‐36; all P < 0.0001) while those receiving SOF+RBV showed moderate decline in some of their PRO scores (−4.8% in physical functioning of SF‐36, −4.4% in fatigue score of FACIT‐F, both P < 0.001). Patients who achieved sustained virologic response with LDV/SOF also showed improvement of PROs (average +5.1%) while those treated with SOF/RBV showed less or no improvement (average +1.4%). In a multivariate analysis, in addition to depression and fatigue, receiving SOF+RBV ( vs LDV/SOF) was independently associated with more PRO impairment during treatment (beta −6.1 to −12.1%, P < 0.001). Hence, HIV–HCV patients treated with LDV/SOF show significant improvement of their health‐related quality of life and other patient‐reported outcomes during treatment and after treatment cessation.